Avaliação da logística de distribuição de produtos em uma empresa de e-commerce - Pileggi, Gisele Castro Fontanella; Rosa, Renata de Oliveira (Revista Gestão da Produção Operações e Sistemas, 2007)
All enterprises, either physically or virtually established, face, on a daily basis, problems that involve the allocation of vehicles and the schedule for the sequence of their assistance services. In general, the purpose is to improve the process efficiency, thus reducing costs and increasing the quality of the services offered. In this context, it is defined the Vehicle Routing Problem (VRP), which consists of assigning routes, starting and finishing the process in a warehouse or distribution center, considering all the problems’ restrictions leading it to the least cost possible. In order to solve this problem, heuristic methods are used, due to the difficulty in applying the exact algorithms to practical problems. A case study was accomplished in a physical and virtual enterprise, located in the city of São Paulo, with the purpose of evaluating its distribution process. A mathematical model for the VRP (BODIN et al., 1983) was implemented, by using the LINGO modeling language. The solutions obtained by the enterprise were compared with the ones obtained by the Clarke and Wright method (1964), and by the solutions obtained by the LINGO. The results demonstrate the applicability of these methods for minor practical problems. Keywords: Logistics; Electronic commerce; Vehicle Routing Problem.